On attaining the prescribed quality of a controlled fourth order system - Kapustyan, Vladimir; Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we discuss a method of auxiliary controlled models and its application to solving some robust control problems for a system described by differential equations. As an illustration, a system of nonlinear differential equations of the fourth order is used. A solution algorithm, which is stable with respect to informational noise and computational errors, is presented. The algorithm is based on a combination of online state/input reconstruction and feedback control methods.
Keywords: auxiliary models; feedback control; online reconstruction